Demand analysis for competences in the field of information technologies from leading Russian companies - L. A. Konstantinova; I. V. Kramarenko (E-Management)
At the present stage of development of information technologies, the study of the need for qualified personnel is becoming more and more popular. At the same time, there is a problem of determining the compliance of specialists’ training level in the field of information technology with the requirements of employers. The article presents the results of a study of the demand for competencies in this field from leading Russian companies. The purpose of the study is to determine the generalized requirements for job seekers in the labor market and the formation of lists of key skills for each of the specialties (professional groups) in the field of information technology. An algorithmic solution is proposed for analyzing the demand for competencies and determining the most demanded skills for various areas. The proposed algorithm is implemented on the example of data on vacancies of the Yandex and VK Group companies, collected from open sources. Data collection was carried out by a modified method: the initial array was formed automatically using the ParseHub parser and corrected manually. The grouping of data was carried out according to the most demanded IT-specialties and according to the generalized formulations of the requirements for these specialties. The key skills of specialists in relevant IT-areas have been identified. The study uses a combination of theoretical and empirical methods. The above algorithm and the results of aggregating groups of vacancies for IT-specialists and their professional competencies demanded by employers can be used for a deeper analysis of demand in the labor market and taken into account when forming the competencies of students in information technology training programs.